Comparative study of municipal solid waste disposal in three Chinese representative cities. (1st May 2020) - Duan, Ning; Li, Dan; Wang, Ping; Ma, Wenchao; Wenga, Terrence; Zhong, Lei; Chen, Guanyi
Abstract: China is facing severe environmental problems, the total municipal solid waste (MSW) generation has dramatically increased and presented great challenges all over the country. Cities have different characteristics in MSW components, generation quantity, influencing factors and disposal ways. Beijing, Guangzhou and Lhasa of Beijing-Tianjin-Hebei economic circle, Pearl River Delta economic zone, and Qinghai-Tibet plateau regions were selected as representative cities, to compare and analyze the features, influencing factors to the MSW generation quantities, and its components by grey correlation analysis. Predictions of MSW generation quantities for Beijing, Guangzhou and Lhasa in 2025 would be 1251.22, 704.71 and 71.040 million tons, respectively, made by BP (back propagation) nerve work using MATLAB software. Results showed that the main indicators of influencing factors to MSW in three cities were all of economic development levels, population and investments of government input. Based on the analysis of internal relationship and characteristics of MSW, some barriers of MSW management were analyzed, and recommendations were given. Our study analyzed the influencing factors and forecasted quantities of MSW generation in representative cities in China, providing valuable evidences for the severe MSW disposal situation of different economic zones in China. Highlights: Socioeconomic factors of MSW generation in different economic zones of China were studied by GCA. MSW generation in Beijing, Guangzhou and Lhasa were predicted by BP nerve network. Barriers, challenges and recommendations of MSW treatment and management were provided.